MTHFR, prothrombin and Factor V gene variants in Turkish patients with coronary artery stenosis - (:unkn) unknown (SOC BRASIL GENETICA, 2008)
Many epidemiological studies have reported an association between hemostatic factors and risk of both coronary and peripheral artery diseases. Using polymerase chain reaction and restriction fragment length polymorphism (PCR-RFLP) analysis, we investigated the association between coronary artery disease and polymorphisms in the methylenetetrahydrofolate reductase (MTHFR C677T and A1298C), prothrombin (G20210A), and factor V (A4070G) genes. We screened these gene variants in 174 subjects who had undergone coronary angiography - 115 patients with patent coronary artery disease (grade 3 vessel disease, i.e., significant coronary stenosis), and 59 healthy controls with grade 0 vessel disease. The analysis of our data did not show any statistically significant association between coronary artery disease (CAD) and the investigated polymorphisms.
Keywords: genetic polymorphism; coronary disease; MTHFR gene; prothrombin gene; Factor V gene; METHYLENETETRAHYDROFOLATE REDUCTASE GENE; VENOUS THROMBOSIS; COMMON MUTATION; RISK-FACTORS; DISEASE